Medicinal plants with cholesterol-lowering effect marketed in the Buenos Aires-La Plata conurbation, Argentina: An Urban Ethnobotany study - Hurrell, Julio Alberto; Puentes, Jeremías Pedro; Arenas, Patricia Marta (Ethnobiology and Conservation, 2015)
This contribution presents 82 species of medicinal plants whose products are sold and consumed as cholesterol-lowering in the Buenos Aires-La Plata conurbation, Argentina. The hypocholesterolemic effect is relevant because the high level of blood cholesterol is one of the major risk factors for cardiovascular diseases, leading causes of death and disability almost worldwide. The species were selected from their locally assigned use, obtained from interviews with informants, data labels, prospectus and leaflets of products, and information diffused in the media, specially the Internet. Furthermore, a bibliographic review on scientific studies that validate the biological activity and effects of each species was accomplished. The theoretical framework of this research argues that urban botanical knowledge comprising some knowledge linked to traditions of various immigrants segments (invisible to most of the local population), and other non-traditional knowledge (visible). The evaluation of these kinds of knowledge is approached from the plant products circulation in the restricted circuits of immigrants (Bolivian and Chinese for this contribution) and the general commercial circuit, so that products that pass from the first circuit to the second gain visibility. The movement of plant products that acquire visibility also expressed the botanical knowledge transmission from one context to another, a transmission enhanced and accelerated by the media. In this frame, the visibility levels of plant products considered hypocholesterolemic in the study area are discussed.